Analisis Konten Youtube Batarbangan sebagai Media Penyebaran Informasi Kepada Masyarakat - Sherlyani, Sherlyani; Riswari, Citra Rani Angga (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study aims to analyze the content of YouTube Batarbangan as a medium for disseminating information to the people of Balangan Regency. The research method used in this study is descriptive qualitative research, and the analysis method uses content analysis. Researchers collect data through interviews, observations, and documentation. Researchers use purposive sampling techniques to select data sources based on predetermined criteria. One informant from the Batarbangan production team and two informants from the Balangan Regency community who watch Batarbangan content. Batarbangan content is produced using established standard operating procedures. In conclusion, the YouTube channel Media Center Pemkab Balangan has become essential in disseminating information to the people of Balangan Regency. The YouTube channel Media Center Pemkab Balangan is crucial in providing information to the people of Balangan Regency. Keywords: Batarbangan, Balangan Regency, Media Center Pemkab Balangan, Information Dissemination, Youtube